Plant poisoning in domestic animals: epidemiological data from an Italian survey (2000–2011). (1st June 2013) - Caloni, F.; Cortinovis, C.; Rivolta, M.; Alonge, S.; Davanzo, F.
Abstract : An Italian epidemiological study based on the human Poison Control Centre of Milan (Centro Antiveleni di Milano (CAV)) data related to domestic animal poisoning by exposure to plants, was carried out in collaboration with the Veterinary Toxicology Section of the University of Milan. It encompasses a 12‐year period, from the beginning of 2000 to the end of 2011. Calls related to toxic plants accounted for 5.7 per cent of total inquiries (2150) received by CAV. The dog was the most commonly poisoned species (61.8 per cent of calls) followed by the cat (26 per cent). Little information was recorded for other species. Most exposures (73.8 per cent) resulted in mild to moderate clinical signs. The outcome was reported in only 53.7 per cent of cases, and fatal poisoning accounted for 10.6 per cent of these cases. Glycoside, alkaloid, oxalate, toxalbumin, saponin, terpene and terpenoid‐containing plants were recorded and found to be responsible for intoxication. Cycas revoluta, Euphorbia pulcherrima, Hydrangea macrophylla, Nerium oleander, Rhododendron species and Prunus species were the plants most frequently involved. Epidemiological data from this Italian survey provide useful information on animal exposure to plants and confirm the importance of plants as causative agents of animal poisoning.